Determinants of Food Security Status of Maize-Based Farming Households in Southern Guinea Savannah Area of Oyo State, Nigeria. - Oluwayemisi Abidemi Onasanya; Oluwakemi Adeola Obayelu (Turkish Journal of Agriculture: Food Science and Technology)
Nigeria is one of the countries in sub-Saharan Africa with insufficient food and high food import bill, which have debilitating effects on the productive capacity of the citizens. Maize is the most important cereal after rice and its production contributes immensely to food availability on the tables of many Nigerians. This study examined the contribution of maize production to household food security status of rural maize-farming households in the southern guinea savannah of Oyo state, Nigeria. A multistage sampling procedure was used to select 200 farm households and the data were analysed using descriptive statistics, recommended daily calorie requirement (RDCR) approach, Logit model. Results showed that about three-quarters of the households were food secure and were able to meet the recommended calorie intake of 2260Kcal per capita per day. The shortfall index (P) which measures the extent of deviation from the food security line, indicated that the food secure households exceeded the RDCR by 65%, while the food insecure households fell short of the RDCR by 31%. The logit model showed that maize output, gender, primary occupation of the farmer, farm size and farming experience had a positive influence on food security status while age had a negative influence on the food security status of maize-based farming households in the Southern Guinea Savannah of Oyo State, Nigeria. This suggests need for specific support to improve maize production